METHOD OF IMPROVING TECHNICAL MOVEMENTS BY DEVELOPING WRESTLERS' QUICK STRENGTH QUALITIES (E Global Congress, 2023)
This article explores a method for enhancing technical movements in wrestling by improving the quick strength qualities of wrestlers. The author discusses the importance of quick strength in executing effective moves and provides strategies for developing this attribute through various training techniques.